Pengembangan Model Manajemen Majelis Taklim dalam Meningkatkan Kualitas Pendidikan Agama Islam di Majelis Taklim - Nurhidayah Husna; Syafnan; Hamdan Hasibuan (Sekolah Tinggi Ilmu Tarbiyah Padang Lawas Gunung Tua, 2024)
This study aims to assess the initial condition and develop a management model for majelis taklim (Islamic study groups) to improve Islamic religious education in Batang Natal District. The research found that the current learning process lacks proper evaluation and feedback systems, and there is no structured way to gather input from participants. While majelis taklim have strong potential to enhance religious understanding in the community, their delivery remains monotonous and without written materials. Using a field research method combined with Research and Development (R&D), this study created a new management model. The findings reveal that religious lectures (tausiyah) are still generic and mostly one-way in communication. Two experts assessed the developed model, scoring it 86% for media, 93% for content, with an average of 92.5%. These scores suggest that the model is both relevant and feasible for improving the quality of Islamic education in majelis taklim settings.